Editorial: social network analysis and economic geography$dpositional, evolutionary and multi-level approaches - Glückler, Johannes; Doreian, Patrick (Journal of economic geography, 2016)
Although social network analysis has gained popularity in economic geography over the last decade, most of these applications focused on analyzing the character